A case study on the low-cost housing with special emphasis on the low-cost flats - Jaya, bin Batu. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This study will benefit the Government agencies in general and the SHDC in particular, as it would provide a guideline for implementing future Low-Cost Flats projects. In addition, the public, especially the low-income groups, will benefits as their plight for more low-cost housing will be given serious consideration by the agencies concerned.